Inflammatory activity following motor progression due to critical CNS demyelinating lesions. (June 2021) - Nayak, Shreya; Sechi, Elia; Flanagan, Eoin P; Messina, Steven; Kassa, Roman; Kantarci, Orhun; Weinshenker, Brian G; Keegan, B Mark
Background: New inflammatory activity is of unclear frequency and clinical significance in progressive multiple sclerosis (MS); it is uncertain in patient cohorts with motor progression due to critical demyelinating lesions. Objectives: The aim of this study is to determine the likelihood of central nervous system (CNS) inflammatory activity, assessed by new clinical relapses or active magnetic resonance imaging (MRI) lesions, following onset of motor progression due to critical demyelinating lesions. Methods: Patients with progressive upper motor neuron impairment for ⩾1 year attributable to critical demyelinating lesions with single CNS lesion (progressive solitary sclerosis (PSS)), 2 to 5 total CNS demyelinating lesions (progressive "pauci-sclerosis" (PPS)), or >5 CNS demyelinating lesions and progressive exclusively unilateral monoparesis or hemiparesis (PUHMS) were identified. Clinical data were reviewed for acute MS relapses, and subsequent MRI was reviewed for active T1-gadolinium-enhancing or T2-demyelinating lesions. Results: None of the 91 patients (22 PSS, 40 PPS, 29 PUHMS) identified experienced clinical relapses over a median clinical follow-up of 93 months (range: 12–518 months). Nine patients (10%) developed active lesions over median 84 months radiologic follow-up (range: 12–518 months). Active lesions occurred in 24% PUHMS, 5% PSS, and 3% PPS cohorts. Conclusion: New inflammatory activity, defined by active lesions and clinical relapses following motor progression in patients with critical demyelinating lesions, is low. Disease-modifying therapies that reduce demyelinating relapses and active MRI lesions are of uncertain benefit in these cohorts.